2020
DOI: 10.3390/molecules25081949
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Cell Microcarriers Based on Chitosan/Polyester Graft-Copolymers

Abstract: Self-stabilizing biodegradable microcarriers were produced via an oil/water solvent evaporation technique using amphiphilic chitosan-g-polyester copolymers as a core material in oil phase without the addition of any emulsifier in aqueous phase. The total yield of the copolymer-based microparticles reached up to 79 wt. %, which is comparable to a yield achievable using traditional emulsifiers. The kinetics of microparticle self-stabilization, monitored during their process, were correlated to the migration of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Microcarriers offer much higher surface-area-to-volume ratios when compared to traditional static culture systems, which, in return, lead to higher cell densities and lower volumetric footprints. Microcarriers have been predominantly produced using the batch emulsion polymerization method from various materials, including dextran, [7] glass, [8] poly(d,l-lactide) (PDLA), [9] collagen, [10] and polystyrene. [11] Although this approach has a high production rate, the polydispersity and batch-to-batch variation of the microcarrier size and morphology necessitates the addition of a downstream purification process to obtain microcarriers with An effective treatment of human diseases using regenerative medicine and cell therapy approaches requires a large number of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Microcarriers offer much higher surface-area-to-volume ratios when compared to traditional static culture systems, which, in return, lead to higher cell densities and lower volumetric footprints. Microcarriers have been predominantly produced using the batch emulsion polymerization method from various materials, including dextran, [7] glass, [8] poly(d,l-lactide) (PDLA), [9] collagen, [10] and polystyrene. [11] Although this approach has a high production rate, the polydispersity and batch-to-batch variation of the microcarrier size and morphology necessitates the addition of a downstream purification process to obtain microcarriers with An effective treatment of human diseases using regenerative medicine and cell therapy approaches requires a large number of cells.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of fractions after separation in acidic aqueous media by elemental analysis showed that about 17% chitosan in terms of the amount taken lose solubility in solvents traditional for chitosan which limits their processability by methods classical for chitosan. However, hydrophobization allows the use of standard methods for molding polyester materials which cannot be used for the production of materials from unmodified chitosan, that is, molding methods based on the affinity of copolymers for chlorine-containing solvents and their processability by melt technologies [108][109][110]. Hot pressed films showed good mechanical properties.…”
Section: Copolymers Of Chitosan With Polylactide and Materialsmentioning
confidence: 99%
“…Another significant advantage of solid-state reactive blending is the possibility to obtain multicomponent systems containing proteins or other polymers and stabilized by in situ formed graft copolymer fractions. Hybrid systems of chitosan with oligolatide/polylactides containing collagen were obtained by this method, gelatin, and polycaprolactone show promise for the production of biodegradable and biocompatible materials of various shapes for use in regenerative medicine [109][110][111][112][113].…”
Section: Copolymers Of Chitosan With Polylactide and Materialsmentioning
confidence: 99%
“…By varying the conditions of synthesis it is possible to control the speed of scaffold degradation and its physico-chemical properties (solubility, pH sensitivity). In particular, copolymers of chitosan, gelatin, and poly(lactic acid) (CGP) are relevant biodegradable carriers of hydrophobic nature which allows delivery of hydrophobic drugs with a high loading capacity [ 15 , 16 , 17 , 18 , 19 , 20 ]. One of the notable representatives of natural polymers is chitosan, which currently has broad application in production of biomaterials and various drug delivery systems [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%